QASHQADARYO VILOYATIDA TARQALGAN MOLLYUSKALAR FAUNASI - Bektashev, SH.M.; Ochilov , Xoliqul (Actual problems and prospects of the study of the fauna, 2024)
Analysing spreading of mollusca in Kashkadarya region of Uzbekistan. Therefore region commont all types of land and water clams Bioecology studied. However, the number of common land and the importance of the world of flora and fauna in the water clams spread across the landscape and the importance of cllan drinking water werc studied. Uzbekistan mollusks fauna and ecology malakolog scientific work being carried out by scientists.